2023
DOI: 10.1002/tcr.202200274
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalyst Fabrication Using Metal Nanoparticles Prepared in Ionic Liquids

Abstract: Metal nanoparticle‐based electrocatalysts are widely used in electronic devices, which serve for electrochemical reactions like oxygen reduction reaction, alcohol oxidation and CO2 reduction reaction. These catalyst‐dependent reactions are the key of the emerging clean energy systems. Catalyst design and synthesis therefore have received keen attention in past decades. We are motivated to study synthesis approaches of metal nanoparticle‐based electrocatalysts using ionic liquids (ILs), which are promising solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
0
1
0
Order By: Relevance
“…16. [51][52][53][54][55][56] Our detailed experiments revealed that the IL layer, which remains after cleaning, acts as a binder between the Pt nanoparticles and the carbon support and impedes their direct contact that enhances carbon support corrosion. 54 When the carbon materials having inert surfaces are used as carbon substrates for cathode electrodes in fuel cells, it is anticipated to decelerate oxidative deterioration of the carbon substrates that occurs when a more positive potential is applied to the electrode than the potential in normal operation.…”
Section: Preparation Of Pt Nanoparticles Electrocatalyst On Carbon Ma...mentioning
confidence: 89%
“…16. [51][52][53][54][55][56] Our detailed experiments revealed that the IL layer, which remains after cleaning, acts as a binder between the Pt nanoparticles and the carbon support and impedes their direct contact that enhances carbon support corrosion. 54 When the carbon materials having inert surfaces are used as carbon substrates for cathode electrodes in fuel cells, it is anticipated to decelerate oxidative deterioration of the carbon substrates that occurs when a more positive potential is applied to the electrode than the potential in normal operation.…”
Section: Preparation Of Pt Nanoparticles Electrocatalyst On Carbon Ma...mentioning
confidence: 89%
“…Ionic liquids (ILs), recognized as environmentally friendly solvents and functional materials, have attracted substantial attention in various scientific domains, including chemistry, biology, physics, and engineering. ILs serve diverse functions, such as catalysts, solvents, and catalyst carriers, and many catalytic reactions can be efficiently carried out in ionic liquid systems. Because of their high thermal stability, lack of volatility, reusability, and low vapor pressure, ILs offer substantial advantages for the liquid-phase catalytic synthesis of isocyanates. Han et al conducted a thermal analysis to explore the changes in mass within the ionic liquid and organic solvent during the heating process while investigating the thermal decomposition of methyl 1,6-adipic carbamic acid (MHDC) in various ionic liquid media using Bi 2 O 3 /Fe 2 O 3 as a catalyst, as illustrated in Figure .…”
Section: Catalyst For the Thermal Decomposition Of Carbamatementioning
confidence: 99%